2002
DOI: 10.1097/00008390-200212000-00006
|View full text |Cite
|
Sign up to set email alerts
|

PTEN inactivation is rare in melanoma tumours but occurs frequently in melanoma cell lines

Abstract: Deletions detected in cytogenetic and loss of heterozygosity (LOH) studies indicate that at least one tumour suppressor gene maps to the long arm of chromosome 10. Previous deletion mapping studies have observed LOH on 10q in about 30% of melanomas analysed. The PTEN gene, mapping to chromosome band 10q23.3, encodes a protein with both lipid and protein phosphatase activity. Somatic mutations and deletions in have been detected in a variety of cell lines and tumours, including melanoma samples. We performed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 28 publications
4
23
0
2
Order By: Relevance
“…S3A). However, consistent with prior DNA sequencing analyses of short-term melanoma cultures and primary tumors (40,41), only 8 of 78 lines examined by sequencing contained inactivating PTEN mutations; of these samples, only 5 also harbored hemizygous loss and LOH of chromosome 10. Using sample-matched gene expression data, we then examined PTEN mRNA expression in relation to genomic deletion.…”
Section: Resultssupporting
confidence: 72%
“…S3A). However, consistent with prior DNA sequencing analyses of short-term melanoma cultures and primary tumors (40,41), only 8 of 78 lines examined by sequencing contained inactivating PTEN mutations; of these samples, only 5 also harbored hemizygous loss and LOH of chromosome 10. Using sample-matched gene expression data, we then examined PTEN mRNA expression in relation to genomic deletion.…”
Section: Resultssupporting
confidence: 72%
“…PTEN regulates PIP 3 levels, and its inactivation results in accumulation of PIP 3 , AKT hyperphosphorylation, and enhanced cell survival/ proliferation. In melanoma, allelic loss or altered expression of PTEN comprises 20% and 40% of melanoma tumors, respectively (Pollock et al 2002;Mikhail et al 2005;Slipicevic et al 2005;Goel et al 2006), although somatic point mutations and homozygous deletions are rarely observed. Functionally, ectopic expression of PTEN in PTEN-deficient melanoma cells can abolish phospho-AKT activity, induce apoptosis, and suppress growth, tumorigenicity, and metastasis (Robertson et al 1998;Stewart et al 2002;Stahl et al 2003; for review, see Robertson 2005).…”
Section: Pten Negative Regulator Of Phosphatidylinositol 3-kinase (Pmentioning
confidence: 99%
“…Homozygous CDKN2A deletions were identified in 27/47 cell lines emphasizing their importance in melanoma cells and in vitro establishment. Although frequent in cultured cells, PTEN homozygous deletions or somatic mutations are less common in primary melanomas, suggesting that this is a late genetic event or that epigenetic mechanisms are responsible for PTEN silencing in primary tumors (Pollock et al, 2002). Moreover, PTEN is likely not the only target gene on chromosome 10.…”
Section: G Jönsson Et Almentioning
confidence: 99%